Decision Support System For Selecting School Majors In Man Using The Weighted Aggregated Sum Product Assessment Method - Rifky Firzani Marpuang; Wahyu Fuadi; Hafizh Al Kautsar Aidilof (Proceedings of International Conference on Multidisciplinary Engineering (ICOMDEN), 2024)
Determining school majors at Madrasah Aliyah Negeri (MAN) is an important process that must consider various factors such as academic grades, interests, and talents of students. However, the determination of the applicable majors still has problems due to several factors such as the environment or parents' requests so that the selection of students' majors is not in accordance with the abilities and talents of students. The selection of majors is also still done manually, so it is less efficient and takes a long time. This research aims to design and build a web-based Decision Support System (DSS) using the Weighted Aggregated Sum Product Assessment (WASPAS) method that is useful for helping schools determine majors that are in accordance with student abilities. This decision support system combines various criteria such as report card scores, academic test results, and practical skills to provide optimal majoring recommendations. The WASPAS method was chosen because of its ability to combine the Weighted Sum Model (WSM) and Weighted Product Model (WPM) methods, which results in more accurate calculations. The calculation test results show that the system built is able to provide major recommendations more quickly and effectively compared to the manual method. This system is expected to help schools in managing student majors more efficiently and objectively.